Storytellers - Yurkovic, Diana; Photographed by Foley, Mary (Australia Shortland Publications, 1998)
Looks at one particular storyteller who tells her stories using animals and people figurines which she makes out of clay. Includes a dough recipe. Suggested level: junior, primary.
Keywords: Storytellers -- Storytellers in art